Development of novel therapeutic and diagnostic approaches utilizing tools from the physical sciences - Malalasekera, Aruni Peiris (Kansas State University, 2016)
Numerous Proteases are implicated in cancer initiation, survival, and progression. Therefore, it is important to diagnose the levels of protease expression by tumors and surrounding tissues, which are reflected in blood and tissue samples. Nanoplatforms for Cathepsin(CTS) B and L, matrix metalloproteinases(MMP) 1, 2, 3, 7, 9, 13 and urokinase plasminogen activator(uPA) detection have been synthesized. Nanoplatforms feature a central dopamine-coated core/shell Fe/Fe₃O₄ nanoparticle. Cyanine 5.5 is permanently tethered to the dopamine ligands via amide bonds. Tetrakis(4-carboxy-phenyl)porphyrin (TCPP) is co-tethered to Fe/Fe₃O₄/dopamine by means of protease consensus sequences. In the presence of a relevant protease sequence, it is cleaved, releasing TCPP from the nanoplatform. In contrast, Cy 5.5 will remain permanently tethered to the nanoparticle. Therefore, an extensive increase of emission intensity of the fluorescence signal from TCPP is observed. This permits the detection of the activity of proteases at femtomolar levels in biospecimens by fluorescence spectroscopy. 46 breast cancer and 20 healthy human blood serum samples were analyzed. Based on the expression pattern of analyzed enzymes, human breast cancer can be detected at stage I. By monitoring CTS B and L stage 0 detection may be achieved. This study demonstrates the feasibility of minimally invasive successful early cancer diagnosis. Immunosuppression is one of the hallmarks of aggressive cancers. Arginase is overexpressed in cancer patients, resulting in systemic immunosuppression. Two nanoplatforms for arginase detection have been synthesized. Both feature a central dopamine-coated core/shell Fe/Fe₃O₄ nanoparticle to which cyanine 7.0 or cyanine 7.5 is tethered via amide bonds. In both nanoplatforms, cyanine 5.5 is linked to the N-terminal of the peptide sequence GRRRRRRRG. Arginine (R) reacts to ornithine (O) in the presence of arginase. According to our results obtained from fluorescence spectroscopy, the oligopeptides GRRRRRRRG and GOOOOOOOG differ in their chain dynamics. In the presence of arginase, and dependent on arginase activity, fluorescence increase of both nanoplatforms is observed, which is an indication that proton-transfer quenching decreases when arginine gets converted to ornithine. The novel assays permit the detection of active arginase within an hour. Additionally, Förster Resonance Energy Transfer (FRET) is observed in nanoplatforms featuring cy 5.5/7.0 pairs, resulting in picomolar detection limits. This is the first example of a “post-translational” enzyme sensor, in which the tether is subjected to chemical transformations of the aminoacid side chains and not cleaved by an enzyme, resulting in the modified mobility of the tether. The nanoplatforms do not show a fluorescence increase when incubated with NO-reductase, an enzyme indicative of immunoactivation, which also uses arginase as substrate. Copper dependent inhibitory activity of 10000 compound library has been studied against of Staphylococcus aureus. 53 copper- dependent hit molecules were recognized featuring extended thiourea core structure with NNSN motif. NMR titrations, UV/Vis studies have been performed for characterization of metal complexation and structure modeling. Chemoinformatic meta-analysis of the ChEMBL chemical database confirmed the NNSNs as an unrecognized staphylococcal inhibitor, in spite of other compound groups in chemical screening libraries. This will lead to the development of novel class of antibacterial agents against Staphylococcus aureus.
Keywords: Breast cancer diagnostics; Biophotonics; High throughput diagnostics; Copper-dependent drug activation; Nanophotonics; Arginase detection